The Centenary of the Discovery of Insulin: An Update on the Quest for Oral Delivery - Brayden, David J. (Frontiers in Drug Delivery, 2021)
Not many topics in drug delivery science have exercised so many pharmaceutical, formulation, and bioengineering minds than the oral delivery of macromolecules, especially when insulin is the focus. The year 2021 marks a hundred years since the discovery of insulin by Banting and Best to treat Type 1 diabetes (Vecchio et al. 2018). Repeated efforts to deliver it orally since then have met with failure, with disappointment ultimately resulting from encouraging preclinical studies in the 1980s. Here, the barriers to synthesizing successful oral insulin formulations are discussed. It is apparent that this peptide has chemistry and pharmacology features that make its oral delivery one of the toughest challenges in delivery science. At this seminal point in its history, the question is whether oral delivery of insulin will ever be possible, or even if this quest is still desirable?